Application of the Constitutional Court's decision on the recognition of the flow of trust in Indonesia in order to realize SDG's 2030 points 16 (Peace, Justice, and Strong Institution) Case Study in Cening Village, Singorojo District, Kendal Regency - Wira Pradana, Tirta Mulya (Universitas Negeri Semarang, 2018)
Intolerance and discrimination based on religion and belief, by the United Nations in